THE STUDY PHENOMENOLOGY OF THERAPY INCREASED APPETITE TODDLER MALNUTRITION IN SUMBERTLASEH DANDER BOJONEGORO - Luthfia, Erien; Azizah, Nur (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2018)
Being to face a great feeding on of under fives who prolonged can result in an influence to the growth of physical and intellectual development. When it does take place continue can affect public health system and resulting in malnutrition or undernourishment in toddlers. The objective the reasearch is to uncover therapy increased appetite for the lacking nutritive children under five years old.A qualitative approach with descriptive phenomenology design with the primary informants families that have children under five main undernourished and supporters informant are public health centre nutritional officers, and village midwives, taken through purposive sampling. Collecting data using in-depth interviews, FGD, observation and documentationStudy.Ten core informants have already participated in this research. Interview recorded later made a transcript of that interview. The study express therapy that could be done by the family to increased appetite is therapeutic dietik undernourished children under five years old, psychological, and pharmacology.This study give the implication that appetite undernourished children under five years old do not hinder endeavors to improve nutrition, if supported by habits the provision of good eating. Need to an increase in the nutrition program and the promotion of health in toddlers families and give education and counseling nutrition to parents who do not eat about increased appetite therapy children under five years old.